New technology and emerging occupations evidence from Asia. - Khatiwada, Sameer (Economics working papers.)
One of the less well-understood channels through which technology affects labor market outcomes is the creation of new types of work. In this paper, we investigate the emergence of new occupations by comparing various classifications of occupations and predicting probabilities to access them given workers' characteristics. Systematic comparisons of successive lists of National Classification of Occupations in India, Malaysia, the Philippines, and Viet Nam find that most new job titles are primarily information and communication technology and data related positions within professional and associate professional occupational divisions. When utilizing microdata of India and Viet Nam, we find that emerging occupations, defined as occupation groups with new job titles, pay higher wages than nonemerging occupations. Further, when using logit models to predict chances of accessing emerging occupations given workers' characteristics, the probability of success is greater for workers who are male, tertiary educated, urbanized, and employed in the service sectors. Adjusted predictions by education and sector show that access to emerging occupations is highest among tertiary-educated workers in services, and that chances of success vary greatly across different age groups.